Layer-by-layer polyelectrolyte microcapsules with tunable release behaviour and versatile encapsulation ability - Luo, Rongcong (2013)
Layer-by-layer (LbL) polyelectrolyte microcapsules with pre-loaded red blood cells (RBCs) ghosts and calcium carbonate (CaCO3) microparticles as template cores were developed in this project. Taking advantage of the unique features of these templates, LbL polyelectrolyte microcapsules with a simplified preparation process, versatile encapsulation capability and tunable release ability are obtained.